Increasing Public Access to University Qualifications: Evolution of The University of the West Indies Open Campus - Thomas, Michael L.; Soares, Judith (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This paper traces the evolution of The University of the West Indies’ Open Campus (UWIOC), which is expected to expand service and increase access to the underserved communities of the Eastern Caribbean. At present, UWI, which caters to the needs of the 16 far flung countries of the Commonwealth Caribbean, has not been able to fully serve these countries, the UWI-12, in a way that is commensurate with their developmental needs. Historically, the institution has been dominated by campus-based education, and its three campuses have been poles of attraction for scholars and scholarship to the significant advantage of the countries in which they are located: Jamaica, Trinidad and Tobago, and Barbados. The University’s creation of an open campus, a fourth campus, enables it to expand its scope, enhance its appeal, and improve the efficiency of its services to individuals, communities, and countries. This new campus, a merger of UWI’s Outreach sector, which comprises the School of Continuing Studies, the Tertiary Level Institute Unit, and The UWI Distance Education Centre, will have a physical presence in each contributing country and will function as a network of real and virtual modes to deliver education and training to anyone with access to Internet facilities.